2015
DOI: 10.1371/journal.pone.0137385
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive STAT3 Phosphorylation in Circulating CD4+ T Lymphocytes Associates with Disease Activity and Treatment Response in Recent-Onset Rheumatoid Arthritis

Abstract: The aim of the present study was to examine constitutive signal transducer and activator of transcription 3 (STAT3) phosphorylation in circulating leukocytes as a candidate biomarker in rheumatoid arthritis (RA). 25 patients with recent-onset, untreated RA provided samples for whole blood flow cytometric determination of intracellular STAT3 phosphorylation, expressed as relative fluorescence units. The occurrence of constitutive STAT3 phosphorylation was evaluated by determining proportion of STAT3-phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…The findings are novel and suggest that activation capability of STAT6 and STAT1 signaling pathways of circulating leukocytes may aid to predict treatment response in RA patients. We also found recently that baseline STAT3 phosphorylation in peripheral blood CD4 + T cells is associated with good treatment response to synthetic DMARDs in recent-onset RA [36]. Immune cell profiling strategies other than above have also been applied to find predictive markers in RA [37].…”
Section: Discussionmentioning
confidence: 97%
“…The findings are novel and suggest that activation capability of STAT6 and STAT1 signaling pathways of circulating leukocytes may aid to predict treatment response in RA patients. We also found recently that baseline STAT3 phosphorylation in peripheral blood CD4 + T cells is associated with good treatment response to synthetic DMARDs in recent-onset RA [36]. Immune cell profiling strategies other than above have also been applied to find predictive markers in RA [37].…”
Section: Discussionmentioning
confidence: 97%
“…42,43 High pSTAT3 levels have also been described for inflammatory diseases. 32,33,[44][45][46] Lovato et al described constitutive STAT3 phosphorylation of intestinal and peripheral blood T-cells from patients with Crohn's disease. 44 Additional studies have further confirmed the important role of STAT3 in Crohn's disease, [46][47][48] and identified the IL-6/STAT3 cytokine signaling pathway as a therapeutic target against chronic inflammation and cancer development in inflammatory bowel disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similar approaches for quantification of constitutive STAT3 phosphorylation have been published previously. 32,33 Alternative methods (e.g., Western blot) were not used because of the restricted donor sample volumes.…”
Section: Ethical Statementmentioning
confidence: 99%
“…We found that baseline phosphorylation of STAT3 in whole blood leukocytes is associated with the treatment response achieved by use of sDMARDs [10]. In the present study, we made progress in studying the JAK-STAT pathway and aimed at elucidating if JAK phosphorylation levels are able to distinguish DMARD-naïve patients with RA who will respond well to sDMARDs from those who will require still other treatment options.…”
Section: Introductionmentioning
confidence: 97%